Determining the correlation between nitrogen content in soil and nitrate accumulation in vegetables - Huong, Nguyen Thi Lan (Vietnam Journal of Earth Sciences, 2014)
Study on the correlation between nitrogen content in soil and nitrate accumulation in farming products have important implications to determine the amount of nitrogenous fertilizer required and appropriate time for harvest, to minimize the effects on human health caused by NO3 - residues in agricultural products. This study was conducted on eight common vegetables grown in Hai Boi commune, Dong Anh district of Hanoi for the demand of city residents. The research results relation between soil nitrogen and nitrate in vegetables is high level, which depends on the species of vegetables and duration after manuring nitrogenous fertilizer. In particular, the correlation coefficient of nitrate concentration in Brassicaceae Juncea and soil nitrogen is highest in comparison with the studied vegetables. After fertilizer supply, nitrate content in vegetables increased very sharply, the highest accumulation was recorded from the 5th to 11th day after fertilization depending different vegetables and decreased gradually after the 11th day of manuring.Therefore, in order to ensure the health of the consumer, it is possible to harvest vegetables from the 15th day after fertilization. At the same time, a small quantity of nitrogenous fertilizer should be used along with phosphate and potassium fertilizers in a balanced way to reduce nitrate content in vegetables under standard permit for safe vegetables as current regulations.